Educational Campaign for Designing Masterplan of Pamaton Site, Tahura Sultan Adam as a Low Carbon Emission Tourism (LCET) Area - Caesarina, Hanny Maria; Thoriq, Tasfin (OMNICODE Journal (Omnicompetence Community Developement Journal), 2025)
As part of Geopark Meratus and Tahura Sultan Adam, Pamaton site holds a significance role in preserving and maintaining its landscape. Pamaton site also has so many important heritage sites from South’s Kalimantan history. On the other hand, the site has so many potentials for Low Carbon Emission Tourism (LCET) which can also enhance economy for the locals. Therefore, this activity is a form of community development to give a clear vision of Pamaton site as an ecotourism area for locals and its local government. The methods were educational campaign about how ecotourism could be a win-win solution to develop Pamaton site while still actively maintaining its natural landscape. Some main concepts to develop LCET in Pamaton site are green buildings, integrating walkability principle with tourism attraction such as hiking and cycling, introducing local culture through local food and urban legend etc. Therefore, Pamaton needs a masterplan for tourism development. For long term planning, Pamaton site has big potential to develop renewable energy due to its exposure of sunrays and wind which needs further research.